How law can recognize culture? The examples from different legal systems - Kleczkowska, Agata (Studia Iuridica Toruniensia, 2015)
There are legal systems which recognize on both the constitutional and legislative level the rights and duties of the cultural minorities. The paper deals with three examples. First of all, the legislation connected with the deferment from military service of Yeshiva students is discussed. The case law of the Supreme Court of Israel is depicted, including the last judgment finally pointing the unconstitutionality of the instrument concerning the deferment. Secondly, the situation of Malays in Singapore is presented. The attention is focused on the fact that despite of being distinguished in constitution and special act devoted only to them, Malays consider themselves to be discriminated in some fields. Thirdly, the Canadian indigenous people example is discussed. This part especially elaborates on the regulation of the Criminal Code and its provisions regarding indigenous people. In the sum up, one needs to underline the problems of national legislations with recognizing fully the needs of cultural minorities.